PENYADARAN GENDER SISWA MA MELALUI LAYANAN INFORMASI DENGAN MEDIA KOMIK DALAM PERSPEKTIF ISLAM - Arofah, Laelatul (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTThe aim of this research is obtained a description the acceptance of user over content and form of media, thus produced fragment comic, a guide book, and sheets evaluation students. This research and development use of measures development of Borg and Gall that consists only seven stages. Conclusion this research is obtained a description the acceptance of the user over content and form of media comic, so produces fragment comic, a guide book, and sheets evaluation with criteria very useful/very right/very clear/very interesting. It’s suggested for further researchers to do research on the effectiveness of using comics to increase gender awareness of students at MA, test the field, and develop fragment comic the gender awareness with a message guidance is more specific. Key Words: Comic, Gender Awareness, MA Students.